Perceived Service Quality in Indonesian Higher Education: A Test of EDUQUAL Model - Teguh Hardi Raharjo; Nina Oktarina; Dian Fithra Permana; Pingkan Anggia Kinaryosih (Dinamika Pendidikan, 2026)
This study aims to evaluate educational service quality at a state university in Indonesia by applying the EDUQUAL model, a framework explicitly tailored for higher education. By integrating the Customer Satisfaction Index (CSI) and Importance-Performance Analysis (IPA), this research assesses overall student satisfaction and delineates specific improvement priorities. A quantitative descriptive approach was employed, surveying 337 undergraduate students. Data were gathered through a structured questionnaire covering five EDUQUAL dimensions: Learning Outcomes, Responsiveness, Physical Facilities, Personality Development, and Academic. Construct validity and reliability were rigorously confirmed via Confirmatory Factor Analysis (CFA). The empirical results yielded a CSI score of 71%, reflecting a satisfactory level of perceived service quality among students. Nevertheless, the IPA matrix revealed that Responsiveness and Physical Facilities are critical priorities requiring immediate institutional intervention to resolve communication delays and infrastructure deficits. Academic and Learning Outcomes dimensions performed optimally and warrant maintenance. Ultimately, this study demonstrates that integrating EDUQUAL with CSI and IPA provides actionable insights for strategic decision-making in university management.